Effects of conventional storage method on Geniotrigona thoracica stingless bee honey properties - Mohamad Ghazali, Nashratul Shera; Yusof, Yus Aniza; Mohd Ghazali, Hasanah; Chin, Nyuk Ling; Othman, Siti Hajar; Chang, Lee Sin; Abdul Manaf, Yanty Noorzianna (Malaysian Society of Agricultural Engineers, 2019)
Most of stingless bee honey contains high moisture content that can easily lead to honey fermentation. This study aims to investigate the applicable of conventional storage method on stingless bee (Geniotrigona thoracica) honey and its effect on storage stability. The Geniotrigona thoracica honeys were stored in a glass bottle at 25˚C for 21 days. The samples were subjected to physicochemical analysis such as moisture content, water activity, viscosity, pH, free acidity, electrical conductivity, colour (L*, a* and b*) and colour intensity. The results obtained indicated that the honey stored in glass bottle slowly reduced the moisture content. The moisture content of honey stored at 25˚C in a glass bottle was reduced from 28.03% to 27.25%. The free acidity of honey increase significantly from106.7 meq/kg to146.3 meq/kg. In conclusion, the amount of water content of honey stored in glass bottle was not largely reduced and consequently changes the physicochemical properties of honey.